Willingness to pay for improved vision in Mozambique. Issue 2 (4th March 2021) - Thompson, Stephen; Naidoo, Kovin; Gonzalez-Alvarez, Carmen; Harris, Geoff; Loughman, James
ABSTRACT: The burden of vision impairment due to uncorrected refractive error (needing spectacles) in Mozambique is known to be significant. To improve the planning and provision of eye health services, a better understanding of how vision is valued by patients is needed. The willingness to pay (WTP) for improved vision through correcting refractive error was investigated in Nampula, Mozambique, using stated choice and bidding game methodologies. The mean WTP values were found to be 388.92 Meticals (US$13) for stated choice and 469.89 Meticals (US$16) for the bidding game. The mean WTP values for rural dwellers were found to be lower than responses from those living in urban areas. If avoidable vision impairment is to be addressed in Mozambique, the cost of services must not be a barrier and the construction of a sustainable spectacle system that delivers for both rural and urban patients must be a priority.